Inflammation and Oxidative Stress in Diabetic Nephropathy: New Insights on Its Inhibition as New Therapeutic Targets - Akira Mima (Journal of Diabetes Research)
Diabetes and insulin resistance can greatly increase microvascular complications of diabetes including diabetic nephropathy (DN). Hyperglycemic control in diabetes is key to preventing the development and progression of DN. However, it is clinically very difficult to achieve normal glucose control in individual diabetic patients. Many factors are known to contribute to the development of DN. These include diet, age, lifestyle, or obesity. Further, inflammatory- or oxidative-stress-induced basis for DN has been gaining interest. Although anti-inflammatory or antioxidant drugs can show benefits in rodent models of DN, negative evidence from large clinical studies indicates that more effective anti-inflammatory and antioxidant drugs need to be studied to clear this question. In addition, our recent report showed that potential endogenous protective factors could decrease inflammation and oxidative stress, showing great promise for the treatment of DN.